The Role of the Peradi Utama Advocate Organization in Sustainable Human Resource Development - Rizkia, Nanda Dwi; Fardiansah, Hardi; Furie, Wulan (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research has the aim that a healthy advocate organization should provide benefits for the welfare of its members. Law Number 18 of 2003 concerning advocates, especially in chapter 10, has clearly stated the definition, function and authority of an advocate organization, article 28 paragraph 1 of the Law on Advocates, for example organizations Advocates are the only free and independent professional forum for advocates formed in accordance with the provisions of the law. Advocates work to share findings regarding climate change with the public to encourage them to make policy changes, creating a sustainable world for everyone is the goal of an advocate. One of the important roles of advocate organizations is to improve the quality of the advocate profession as mandated by Law No. 18 of 2003 concerning Advocates. Ways to improve the quality and skills of advocates include education and training